Risk factors of mucormycosis in post-COVID-19 patients– A Retrospective study - Shaheen Zafar; Vineet Sinha; Surbhi; Rohit Kumar (Asian Journal of Medical Sciences, 2022)
Background: Rhino-orbito-cerebral mucormycosis was seen in increasing severity in the recent second wave of COVID-19 in India. The incidence of mucormycosis is increased significantly in patients with diabetes. The most common cause attributed to the rise of mucormycosis in COVID-19 patients are uncontrolled diabetes. Lymphopenia and increased levels of certain cytokines, such as IL-6, have been closely associated with the disease severity. Aims and Objectives: The aims of this study were to analyze risk factors involved in Mucormycosis in 2nd wave of COVID-19. Materials and Methods: The study was done in the Mucormycosis ward, Department of ENT, Patna Medical College and Hospital, Patna, between May 2021 and July 2021. A total of 100 patients of both gender and all age groups were taken into the study. Results: Out of 100 patients included in the study, 57% (n=57) of patients had history of steroid intake, while 43% (n=43) had no history. About 41% (n=41) of patients needed oxygen support during treatment,while 59% (n=59) had no history of oxygen inhalation. About 88% (n=88) of patients had prior history of diabetes or detected during treatment, while 12% (n=12) had no prior history of diabetes or detected during treatment. About 91% (n=91)of patients had uncontrolled hyperglycemia, while 9% (n=9) had controlled blood sugar level. Conclusion: Uncontrolled hyperglycemia and delta strain are mainly associated major risk factors that lead to such high number of mucormycosis cases in India (post 2nd wave of COVID-19). Steroid role is not that much significant in our study and oxygen inhalation is not associated with mucormycosis.